2016
DOI: 10.1186/s12903-016-0174-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fixed appliances on oral malodor from beginning of treatment till 1 year

Abstract: BackgroundOrthodontic appliances can enhance plaque accumulation, and this can cause gingival inflammation. Halitosis of oral origin is associated with microbial metabolism on the tongue and in the saliva, dental plaque, and the amount of volatile sulfide-containing compounds. This study used a Halimeter to investigate fixed orthodontic therapy-associated increases in the oral malodor over a year.MethodsThirteen orthodontic patients with Angle Class I malocclusions receiving fixed orthodontic therapy formed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…14 After 27 days, the oral malodor scores had significantly decreased compared to the baseline, although the clinical study indicated an increase after the braces were applied. 3,13 This disparity may be explained by the variability of oral hygiene methodology, considering that the participants were adolescents. Adolescents need a unique approach to be motivated about their oral health issues, which are substantially associated with their social interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 After 27 days, the oral malodor scores had significantly decreased compared to the baseline, although the clinical study indicated an increase after the braces were applied. 3,13 This disparity may be explained by the variability of oral hygiene methodology, considering that the participants were adolescents. Adolescents need a unique approach to be motivated about their oral health issues, which are substantially associated with their social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although some studies have shown a lower occurrence of oral malodor in patients with self-ligating brackets compared to patients using conventional brackets, 12 other studies have indicated that self-ligating brackets have a higher potential for bacterial accumulation. 13 Overall, fixed orthodontic therapy interferes with the occurrence of oral malodor due to elevated levels of bleeding, gingival inflammation and the presence of periodontal pockets. 13 With this reasoning, studies have focused on exploring the oral malodor etiopathogeny in fixed-orthodontic users, in order to determine their particularities and, consequently, conduct an appropriate control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zurfluh et al [ 21 ] found significant differences in organoleptic measurements on the same subjects between the initial visit and at 3 months. Based on a 1-year observation, Sokucu et al [ 12 ] reported that oral malodor in orthodontic patients reached a peak after 7 months and stopped increasing during the ninth month of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some investigators have reported that fixed orthodontic appliances can increase oral malodor, [ 11 , 12 ] and that oral malodor should be regarded as one of potential side effects of orthodontic treatments. Additionally, the effects of self-ligating bracket (SLB) and conventional bracket (CB) systems have been discussed widely, although a previous meta-analysis revealed that SLBs do not outperform CBs in promoting oral health.…”
Section: Introductionmentioning
confidence: 99%